Effects of three basic dimensions of instructional quality on students' situational interest in sixth-grade biology instruction. (August 2018) - Dorfner, Tobias; Förtsch, Christian; Neuhaus, Birgit J.
Abstract: Previous research defined and evaluated three basic dimensions of instructional quality: classroom management, supportive climate, and cognitive activation. This study examined their effects on students' situational interest in videotaped biology instruction from German sixth-grade classes. Additionally, we evaluated the mediating effects of cognitive activation on classroom management and supportive climate using multilevel analyses. Each of the 28 biology classes in our sample had three lessons videotaped while the topic botany was being taught. The three basic dimensions of instructional quality were separately examined using respective rating manuals. Multilevel analyses showed positive total effects of all the three dimensions on students' situational interest. The results also revealed empirical evidence that cognitive activation mediated both the effects of classroom management and supportive climate on students' situational interest. As our findings indicate subject-specific characteristics are necessary to foster students' situational interest, we suggest further studies for deeper examination and analysis of these characteristics. Highlights: Three basic dimensions of instructional quality are defined and often evaluated. The interplay of the three basic dimensions needs to be evaluated. The basic dimensions were independently raised via video rating. All three basic dimensions have positive effects on students' situational interest. Cognitive activation mediates effects of classroom management & supportive climate.